Development of the core occupational adaptabilities through the learning-orientated interaction of employees’ proactivity and organizational support - Yifu Wang; Qian Xu; Peihao Yin; Juan Zhang; Lihua Zhang (Humanities & Social Sciences Communications)
Abstract Core occupational adaptability (COA) is a crucial occupational competency and workplace competitiveness for employees. This study identified significant antecedent variables that impact COA and constructed a structural equation model to test the relationships among these variables. A questionnaire survey was administered to 519 employees from Chinese manufacturing enterprises to validate the model. The results revealed that perceived organizational support (POS), proactive personality (PP), and career-related continuous learning (CCL) positively predicted an employee’s COA. PP and POS indirectly predicted COA through the mediating role of CCL, respectively. Moreover, employees’ age moderated the direct effect between PP and COA positively, while employees’ positions positively moderated the direct effect between POS and COA. This study demonstrated that CCL is critical in enhancing employee initiative, providing organizational support, promoting vocational learning, and improving overall COA levels among employees.